1993
DOI: 10.1093/eurheartj/14.suppl_b.35
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind comparison of a beta-blocker and a potassium channel opener in exercise induced angina

Abstract: This randomized, double-blind, parallel study compared the anti-anginal effects of nicorandil and atenolol in 37 patients with exercise-induced angina pectoris. At the end of a single-blind placebo period, patients were randomized and received either atenolol 50 mg o.d. or nicorandil 10 mg b.d. for 3 weeks. On the third week, the dosage was increased (nicorandil 20 mg b.d. or atenolol 100 mg o.d.) for the final 3-week period. Treadmill exercise tolerance tests were performed immediately before and 2 h after do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… RCT 20–60 mg Angina pectoris 8 20 mg 50% 40 mg 88% 60 mg 67% Raftery et al 1993, Eur. Heart Journal [ 93 ]. RCT 20 mg and 40 mg Angina pectoris 18 11 (61%) Roland 1993, Eur.…”
Section: Headache Induced By K Atp Channels Openermentioning
confidence: 99%
“… RCT 20–60 mg Angina pectoris 8 20 mg 50% 40 mg 88% 60 mg 67% Raftery et al 1993, Eur. Heart Journal [ 93 ]. RCT 20 mg and 40 mg Angina pectoris 18 11 (61%) Roland 1993, Eur.…”
Section: Headache Induced By K Atp Channels Openermentioning
confidence: 99%
“…Gastralgia and nausea only were reported by 10 patients (5.1%) during a one-year period of exposure to nicorandil [25]. In a multi-centre randomised parallel trial, where 57 participants were randomised to nicorandil, no gastrointestinal events were witnessed [26]; no significant reactions were noted in similar studies comparing nicorandil with other calcium channel blockers [27], isosorbide 5-mononitrate, isosorbide dinitrite [28][29][30][31] or-blockers [32][33][34][35][36] or when nicorandil was added to a baseline therapy in settings of unstable angina [37] or acute myocardial infarction [38][39][40][41][42][43].…”
Section: General Gastrointestinal Side-effectsmentioning
confidence: 99%
“…Thus the value of the treatment has been disputed (Fox et al, 2006). Several small randomized trials have shown that Nicorandil prolongs the time to onset of ST-segment depression and exercise tolerance during treadmill exercise testing in patients with stable angina (Di Somma et al, 1993;Meeter et al, 1992;Raftery et al, 1993). Markham et al also have shown that nicorandil prolongs time to the onset of angina, time to 1 mm ST depression, improves exercise duration and reverses ischemia-related impairment in regional wall motion during exercise (Markham et al, 2000).…”
Section: Clinical Applicationmentioning
confidence: 99%